Information aggregation in competitive markets - Lucas Siga; Maximilian Mihm (Theoretical Economics, 2021)
We study when equilibrium prices can aggregate information in an auction market with a large population of traders. Our main result identifies a property of information—the betweenness property—that is both necessary and sufficient for information aggregation. The characterization provides novel predictions about equilibrium prices in complex, multidimensional environments.
Keywords: C72; D44; D82; D83; G14; 330; Auctions; betweenness; competitive markets; information aggregation; rational expectations equilibrium